On the nature of the reentrant effect in susceptibility of mesoscopic cylindrical samples - Gogadze, G.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Theory of the reentrant effect in susceptibility of mesoscopic cylindrical NS samples is proposed, which is essentially based on the properties of the Andreev levels. The specific feature of the quantum levels of the structure is that in a varying magnetic field (or temperature) each level periodically comes into coincidence with the chemical potential of the metal. As a result, the state of the system becomes strongly degenerate and the amplitude of the paramagnetic contribution to the susceptibility increases sharply.